Telecommunications law in the Internet age - Black, Sharon K. (San Francisco : Morgan Kaufmann Publishers, 2002)
For companies in and around the telecommunications field, the past few years have been a time of extraordinary change-technologically and legally. The enacting of the Telecommunications Act of 1996 and the development of international trade agreements have fundamentally changed the environment in which your business operates, creating risks, responsibilities, and opportunities that were not there before. Until now, you'd have had a hard time finding a serious business book that offered any more than a cursory glance at this transformed world. But at last there's a resource you can depend on for in-depth analysis and sound advice. Written in easy-to-understand language, Telecommunications Law in the Internet Age systematically examines the complex interrelationships of new laws, new technologies, and new business practices, and equips you with the practical understanding you need to run your enterprise optimally within today's legal boundaries. * Offers authoritative coverage from a lawyer and telecommunications authority who has been working in the field for over three decades. * Examines telecommunications law in the U.S., at both the federal and state level. * Presents an unparalleled source of information on international trade regulations and their effects on the industry. * Covers the modern telecommunications issues with which most companies are grappling: wireless communication, e-commerce, satellite systems, privacy and encryption, Internet taxation, export controls, intellectual property, spamming, pornography, Internet telephony, extranets, and more. * Provides guidelines for preventing inadvertent violations of telecommunications law. * Offers guidance on fending off legal and illegal attacks by hackers, competitors, and foreign governments. * Helps you do more than understand and obey the law: helps you thrive within it.
Introduction : the new telecommunications environment -- Competition and regulation, a continuing telecommunications cycle -- The Telecommunications Act of 1996 -- Outstanding issues from the Telecommunications Act of 1996 -- The World Trade Organization and its telecommunications-related agreements -- Participating in global telecommunications trade : U.S. import and export laws -- Licensing to protect telecommunications intellectual property -- Privacy -- Encryption -- Cyberlaw : evolving legal issues with the Internet.
Includes bibliographical references and index.
Keywords: Telecommunication -- Law and legislation -- United States; Electronic books